The Imagined Child - Richards, Jo-Anne (My University, 2016)
This PhD comprises a work of fiction and a dissertation, both of which explore childhood, children and parenthood. The Imagined Child, the novel, closely examines the nature of parenthood, the expectations inherent in the parent-child relationship, and the responsibilities that society imposes on parents. It explores the strains of guilt and blame that surround all primary relationships: every child is damaged in some way – through nature and nurture. How they deal with that damage determines the kinds of adults – and ultimately the kinds of parents – they become. The dissertation approaches childhood as a literary device. It explores the ways in which four novelists from different historical periods have characterised and thematised childhood. It presents ‘childhood’ as a social construct and considers the ways in which childhood and parenting have changed in recent, Western history. It then focuses on the research into and literary representations of children in Africa to explore the versions of childhood inherited by African, and particularly South African, children and how this differs from American or European models. Textual analysis was employed to examine the representation of childhood in four texts: Charles Dickens’s David Copperfield (1850), L.P. Hartley’s The Go-Between (1953), Harper Lee’s To Kill a Mockingbird (1960), and Michiel Heyns’s The Children’s Day (2002). An examination of research and literature shows a very different trajectory for childhood in Africa than in Europe, and reveals that childhood on the continent has never been consistent, in life or literature. There is, in other words, no universal “African childhood”. The literary children of South Africa are examined not only to show how differently childhood is experienced in diverse segments of society, but also to measure the temperature of the times. The differing versions of literary childhood, and their varying treatments, provide a gauge for the zeitgeist in South African society from the 1990s. The dissertation argues that an examination of literary children provides insight into the development of a new democracy. The dissertation and the novel, taken together, suggest that through the real and imagined children of literature can be gained a sense of ourselves.
Keywords: Dickens, Charles--1812-1870--Characters--Children; Dickens, Charles--1812-1870--David Copperfield; Lee, Harper--To kill a mockingbird; Heyns, Michiel--The Children's day; Hartley, L. P. (Leslie Poles)--1895-1972--The Go-between; Parent and child in literature; Children in literature; Parent and child; Children